A stochastic analysis of stock price variation assessments in Oando Nigeria, Plc - Amadi*, I.U.; Vivian†, M.J.O. (International Journal of Mathematical Analysis and Modelling, 2023)
This paper applied stochastic analysis of Markov chain in the closing stock price data of Oando Nigeria Plc (2017-2021). The stock prices were transformed into 3-steps transition probability matrix solution for each independent year. The criteria of obtaining future stock price changes of the year were considered. From the analytical solution of stochastic analysis, showed that the closing stock price of 2017 has the highest mean rate of returns and growth rates respectively: 2.4112 and 69%. Also stock prices of 2018 has the best probability of price not changing in the near future: 26% , which is a guide to investor for proper decision making. In all, the impact of future price changes were assessed which shows various levels of pricing effects on the aspect of percentage increase and decrease as it affects the original prices, Oando Nigeria PLC is profit making organization, hence the growth rates are all indexed in millions of naira.